Decision making in urban development: The application of a hybrid evaluation method for a critical area in the city of Turin (Italy). (September 2021) - Bottero, Marta; Assumma, Vanessa; Caprioli, Caterina; Dell'Ovo, Marta
Highlights: An integrated framework is developed to envision future sustainable scenarios of transformation. Quali-quantitative methods are combined into an overall evaluation methodology. The multi-level methodology is performed for a downgrounded area. The evaluation framework supports the design process in a structured way. Abstract: Smart cities and sustainable neighbourhoods are increasingly gaining more attention within policy decisions on urban transformations. In this context, Decision-Makers (DMs) need evaluation methodologies able to support the definition of policies and actions for the future of cities, that focus on a higher degree of life quality and new needs. In this paper, an integrated framework is proposed which combines the Stakeholder Analysis, the STEEP and SWOT analyses (STEEP + SWOT), the Scenario Building and the Multicriteria Decision Analysis approach (MCDA) which can be used to envision sustainable future scenarios for an underdeveloped area in Northern Italy. The adoption of integrated methodologies facilitates the analysis of each phase of the decision problem, from its early stage to the selection of the most suitable scenario according to the context and the stakeholders engaged. With this perspective, the present research is a guiding tool for DMs for the design of transformation/regeneration scenarios with a long-term perspective of sustainable cities and neighbourhoods. From the results obtained, it is possible to build new and unexpected scenarios by combining the main opportunities and strengths of most suitable alternatives.